Simulation of a CFB Boiler Integrated With a Thermal Energy Storage System During Transient Operation - Stefanitsis, Dionisis; Nesiadis, Athanasios; Koutita, Konstantina; Nikolopoulos, Aristeidis; Nikolopoulos, Nikolaos; Peters, Jens; Ströhle, Jochen; Epple, Bernd (Frontiers in Energy Research, 2020)
In the current work, a transient/dynamic 1-dimensional model has been developed in the commercial software APROS for the pilot 1 MWth CFB boiler of the Technical University of Darmstadt. Experiments have been performed with the same unit as well, the data of which are utilized for the model validation. The examined conditions correspond to the steady-state operation of the boiler at 100%, 80% and 60% heat loads, as well as for transient conditions for the load changes from 80% to 60% and back to 80%. Fair agreement is observed between the simulations and the experiments regarding the temperature profiles in the riser, the heat extracted by the cooling lances as well as the concentration of the main species in the flue gases; a small deviation is observed for the pressure drop, which, however, is close to the results of a CFD simulation run. The validated model is extended with the use of a thermal energy storage (TES) system, which utilizes a bubbling fluidized bed to store/return the particles during ramp up/down operation. Simulations are performed both with and without the use of TES for the load path 100%-80%-60%-80%-100% and the results showed that the TES concept proved to be superior in terms of changing load flexibility, since the ramp up and down times proved to be much faster and lower temperature drops between the loads are observed in this case.